VARIANTS OF CLINICAL COURSE AND METHODS OF TREATMENT OF VIRAL HEPATITIS DELTA - Ne’matov Humoyun Abdusalim (Web of Journals Publishing, 2025)
Hepatitis D is an inflammation of the liver caused by the hepatitis D virus (HDV), which requires hepatitis B virus (HBV) for its replication. Hepatitis D infection cannot occur in the absence of HBV. HDV–HBV co-infection is considered the most severe form of chronic viral hepatitis due to more rapid progression towards hepatocellular carcinoma and liver-related death. Vaccination against hepatitis B can prevent HDV infection. HDV has recently been classified as carcinogenic to humans (class I) by the IARC mongraphprogramme, just like hepatitis B and C.
Keywords: Hepatitis D virus, RNA test, intoxication, splenomegaly, jaundice, arthralgia.